Role of the reactive atmosphere during the sol-gel synthesis on the enhancing of the emission quantum yield of urea cross-linked tripodal siloxane-based hybrids - Freitas, Vania T.; Lima, P. P.; Ferreira, R. A. S.; Carlos, L. D.; Pecoraro, Édison [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Zea Bermudez, V. de (Springer, 2014)
Transparent monoliths and films of urea cross-linked tripodal siloxane-based hybrids (named tri-ureasils) were prepared by the sol-gel process, under controlled atmosphere (inside a glove box) and ambient conditions and their structure and optical features were compared. X-ray diffraction data point out that all the materials are essentially amorphous and Si-29 NMR reveal an increase in the condensation degree (0.97) for the hybrids prepared under controlled atmosphere relatively to that found for those prepared under ambient conditions (0.84-0.91). The tri-ureasils are white light emitters under UV/Visible excitation (from 250 to 453 nm) being observed for the composites prepared inside the glove box a significant enhancement (60-80 %) of the absorption coefficient and higher emission quantum yield values (similar to 0.27 and similar to 0.20 for monoliths and films, respectively) relatively to those synthesized under ambient condition.
Keywords: Tripodal organic-inorganic hybrids; Tri-ureasils; Sol-gel; Photoluminescence; Laboratory controlled atmosphere